Development of mathematics teaching materials based on the scientific approach to facilitate students' mathematical problem–solving ability in statistics learning - Tasya Ananda; Sehatta Saragih; Elfis Suanto (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2026)
This study was motivated by students’ low mathematical problem-solving ability, which was caused by inappropriate learning approaches and the lack of teaching materials that support the development of mathematical problem-solving ability. This study aims to produce mathematics teaching materials based on a scientific approach that are valid and practical to facilitate students’ mathematical problem-solving ability in statistics material, specifically measures of central tendency, for Grade VIII SMP/MTs students. This research is development research using the Tessmer model, which consists of preliminary and formative evaluation stages, including self-evaluation, expert review, one-to-one evaluation, and small group evaluation. The instruments used were validation sheets and student response questionnaires. The results of validation by three experts showed that the teaching materials had a very high level of validity, with an average score of 87.4%. Readability and attractiveness tests through one-to-one evaluation, as well as practicality tests through small group evaluation involving 11 students, resulted in an average response score of 89.25%, which was categorized as very practical. These findings show that the developed teaching materials are feasible to use and can support the development of students’ mathematical problem-solving ability. The contribution of this research lies in the explicit integration of the scientific approach into the structure of teaching materials to facilitate mathematical problem-solving ability. The implication of this research shows that developing teaching materials based on the scientific approach can be a strategic solution for improving the quality of mathematics learning at the junior high school level.